The Roman cult of Mithras : the god and his mysteries - Clauss, Manfred, 1945- (Edinburgh University Press, 2000)
"Since its publication in Germany, Manfred Clauss' introduction to the Roman Mithras cult had become widely accepted as the most reliable, and readable, account of this subject. For the English edition the author has updated the work to reflect recent research and new archaeological discoveries."--Jacket